Measurements of The Pediatric Cartilaginous Eustachian Tube: Implications for Balloon Dilation. (26th March 2022) - Yu, Yuan; Geffen, Brent; McCrary, Hilary; Dunya, Gabriel; Rampton, John; Zhang, Chong; Presson, Angela P.; Poe, Dennis; Park, Albert H.
Abstract : Objectives: (1) Measure the cartilaginous Eustachian tube (ET) length using a computed tomography (CT) scan and (2) develop a prediction model to measure this length without the need of a CT scan. Study Design: CT measurements in children. Setting: Children's Hospital. Methods: CT scans were reformatted to project the cranial and caudal limits of the cartilaginous ET. The length was measured in 193 children who underwent a neck CT scan for nonotologic indications. Five physicians independently reviewed all or some of these measures. Four different models based on age, age ranges, weight, and height were created and compared to predict ET length. Results: The cartilaginous ET length was 25.3 ± 3.1 mm for the right and for the left ear. The mean ET length for the females was statistically significantly less than the length in males. The lower ET lengths in children as old as 5 years of age were less than the 2 cm adult criteria used for catheter insertion. All 4 models performed equally well in predicting ET length. Model number 4, which is based on height, was the easiest to calculate ET length. Conclusion: The cartilaginous portion of the pediatric ET can be measured with good precision using reformatted CT images. We caution against using the "adult" criteria of 2 cm for catheter insertion in children, especially those younger than 5 years of age. We recommend using a model utilizing height measures to estimate ET length or direct measurements from a reformatted CT scan. Level of Evidence: NA Laryngoscope, 133:396–402, 2023